Experimental Study on Compressive and Flexural Performances of Polypropylene Fiber-Reinforced Concrete - Yimeng Wei; Yuan Qin; Junrui Chai; Chengyong Xu; Yue Zhang; Xianwei Zhang (Geofluids)
Plain concrete (PC) has the disadvantages of easy cracking and low resistance to deformation. In practical engineering, steel fiber or polymer fiber is usually selected to improve the tensile and crack resistance of concrete. In this study, the polypropylene fiber (PPF) was added to the concrete with the content of 0, 0.6, 0.9, and 1.5 kg/m3. The compressive and flexural tests of PC and PPF-reinforced concrete (PPFRC) at 14, 28, and 60 days of curing were conducted. As the result, when the content of PPF exceeds to 1.2 kg/m3, the workability became worse. The compressive and flexural strength of PPFRC increased compared with PC. However, the increase of strength does not always increase with the increase of fiber content. The uniaxial compressive strength of the PPFRC with the PPF of 1.2 kg/m3 is the optimal at 14- and 28-day ages, which is 20.56% and 11.24% higher than PC, respectively. PPFRC with the PPF of 0.9 kg/m3 is best of all at 60 days, which is 19.68% higher than PC. The flexural strength of the PPFRC-0.9 is the highest. Furthermore, the CFEC and CTI of PPFRC are both higher than those of PC, indicating that it has significant crack resistance and toughness.